STUDI PENENTUAN BOBOT KEPENTINGAN DALAM GROUP DECISION MAKING - , INTAN TIARA DEWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Every day, human face several options to take a decision. Neither individuals, nor in an organization, will be faced many alternatives of choices for the purpose to be achieved. On a groups or organizations, decision making activities are faced to take a strategic decision to get the best alternatives, such as determining suppliers, warehouse location, management strategies and any other strategic decisions. Based on many considerations and the purpose to take best decisions between various considerations, a natural process in which decisions are made more than one person, called group decision making (GDM). But in fact, sometimes a decision bias appear, where one person dominates the groupâs decision, but the decision is not necessarily the right decision. By designing and changing the weights of decision makers based on the common decision, we increase the consensus without forcing the experts to modify their opinions. In this research, the result is a decision making through consensus process has the possibility of a biased decision, where the decision makers dominate the groupâs decision, while the result is necessarily true. Application GDM calculation by designing model weight in each decision makers can avoid the biased decision and improve the value of consensus and decision alternatives generated by GDM calculations. Keywords: group decision making, GDM, preference, decision bias, weight, decision makers, decision analysis, decision theory